Business in a challenging political environment under sanctions : An examination of Finnish companies in Russia 2014-2020 - Kallio, Elias (My University, 2023)
The topic of this thesis is important to understand how the Russian economy, society, as well as the operating environment for foreign, especially the Finnish case companies in Russia have evolved. The research questions in the study try to answer how the political and economic environment has evolved during the research period and what was it in the end of research period as well as how this development has affected the case companies and where the companies were at the end of the research period. The research methods used in this thesis are mostly a combination of qualitative and quantitative approaches. Most of the data used is qualitative, but it is then supported by some quantitative data, e.g., statistics. The effect of sanctions and countersanctions on foreign companies as well as the effect of those on Russian economy have been studied. The research gap this thesis is trying to address falls between those two well studied topics. The political and economic environment has developed negatively during the research period for the case companies. Some of the case companies worsened the situation with the lack of diversification in a high country-risk market environment. The significance of the findings and main theoretical implication of this study lies in the opportunity to explore if operating in such a market environment was worth the country risk.

Tutkielman aihe on tärkeä, jotta voidaan ymmärtää kuinka Venäjän talous, yhteiskunta sekä toimintaympäristö ulkomaisille, erityisesti suomalaisille tutkittaville yrityksille, on Venäjällä kehittynyt. Tutkimuskysymykset pyrkivät tutkielmassa pyrkivät vastaamaan kuinka poliittinen ja taloudellinen toimintaympäristö on Venäjällä kehittynyt tutkimusjakson aikana ja millainen se on ollut tutkimusjakson lopussa sekä kuinka tämä kehitys on vaikuttanut tutkittaviin yrityksiin ja missä asemassa nämä yritykset olivat tutkimusjakson lopussa. Tutkielmassa käytetyt tutkimusmenetelmät ovat pääosin laadullisen ja määrällisen lähestymistavan yhdistelmä. Enemmistö käytetystä aineistosta on laadullista, mutta sitä on tuettu määrällisellä aineistolla, esimerkiksi tilastoilla. Pakotteiden ja vastapakotteiden vaikutusta ulkomaisiin yrityksiin sekä Venäjän talouteen on tutkittu. Tutkimusaukko, jota tämä tutkielma pyrkii paikkamaan, liittyy siihen, että näiden kahden aiheen väliä ei ole tutkittu erityisen paljon. Taloudellinen ja poliittinen ympäristö on kehittynyt tutkittavien yritysten kannalta negatiivisesti tutkimusjakson ajan. Osa tutkittavista yrityksistä pahensi tilannettaan vähäisellä hajautuksella korkean maariskin markkinaympäristössä. Tutkielman löydökset ja tärkeimmät teoreettiset johtopäätökset piilevät mahdollisuudessa tutkia, onko kyseisenlaisella markkinalla toimiminen maariskin arvoista.
Keywords: Russia, economic sanctions